Cultural Revitalisation and Resistance: The Religious Politics of Fela Anikulapo Kuti and Bishop Matthew Kukah - Oladosu, Olusegun Adebolu; Aluko, Oluwasegun Peter; Idowu, Sunday Akintayo (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This paper examines the intersection of cultural revitalization, religious politics, and resistance in the works of two prominent Nigerian figures: Fela Anikulapo Kuti and Bishop Matthew Kukah. Through his music, rituals, and symbolic shrine, Fela championed the revival of African Indigenous Religion, resisting the dominance of foreign faiths, particularly Christianity and Islam, while challenging political corruption and social injustice. In contrast, Bishop Kukah, a Christian cleric, has consistently used his platform to critique political injustice, advocate for freedom and rights, and combat religious hypocrisy. Despite their differing methods – Fela's use of music for cultural and religious revival and Kukah's reliance on the pulpit and public discourse – both figures have sought to combat neocolonial subjugation and promote African self-emancipation. This study provides insights into the complex interplay between religion, politics, and cultural identity in contemporary Nigerian society by comparing and contrasting their approaches.